The Influence of Online Learning Systems on the Efectiveness of Learning According to Islamic Perspective - Amiruddin Amiruddin; Uswatun Hasanah Sitompul; Ayu Azhari; Aldi Bayu Anggara (Universitas Muhammadiyah Enrekang, 2022)
This journal aims to find out whether online learning systems or virtual systems will be very effective or not and find out about the influence of online learning systems from an Islamic point of view. Due to remember that the era of development of technology and information is unavoidable and greatly affects our daily lives. And from the point of view of Islam it is also obligatory to seek knowledge and teach knowledge that we already know and practice. This research uses qualitative research, while the method we use is collecting all information from forms of literacy and other reading materials in the form of scientific articles and so on by utilizing the internet as a source of information livelihoods to make this journal article. The results of this study are that online learning is very effective in today's era because we have to take advantage of existing technology and information, and it depends on how we use it wisely and are able to use media well.